Simulation of quantum growing network / Ong Boon Teong - Ong , Boon Teong (2003)
Over the past 40 years there has been a dramatic miniaturization in computer technology. If current trends continue, by the year 2020 the basic memory components of a computer will be the size of individual atoms. At such scales, the current model of computation, based on a mathematical idealization known as the Universal Turing Machine, is simply invalid. A new field, called "quantum computing" is emerging that is re-inventing the foundations of computer science and information theory in a way that is consistent with quantum physics - the most accurate model of reality that is currently known. Remarkably this new theory predicts that quantum computers can perform tasks exponentially faster than any conventional computer. Moreover, quantum effects allow unprecedented tasks to be performed such as teleporting information, breaking supposedly "unbreakable" codes, generating true random numbers, and communicating with messages that betray the presence of eavesdropping. These capabilities are of significant practical importance to banks and government agencies. lndeed, a quantum scheme for sending and receiving ultra-secure messages has already been implemented over a distance of 30km-far enough to wire the financial district of any major city. Modem microprocessors have to be designed with quantum mechanics in mind in order to ensure that they function correctly. In essence they use quantum effects to ensure that their classical computations are upheld. What no current processor does is to fully exploit quantum effects Recently, it took 1,600 computers communicating over the Internet 8 months to solve the factorisation of a 129-digit number. Should it be possible to build a microprocessor which fully exploits quantum mechanics then it may be possible to carry out such factorisations in remarkably less time. The RSA algorithm, a widely used encryption system, is safe only if such factorisations cannot be performed quickly. Although modem computers already exploit some quantum phenomena they do not make use of the full repertoire of quantum phenomena that Nature provides. Harnessing these phenomena will take computing technology to the very brink of what is possible in this Universe.